<span>=<span><span><span><span><span>(3)</span><span>(x)</span></span>+<span><span>(3)</span><span>(4)</span></span></span>+<span><span>(2)</span><span>(<span>5x</span>)</span></span></span>+<span><span>(2)</span><span>(2)
</span></span></span></span><span>=<span><span><span><span>3x</span>+12</span>+<span>10x</span></span>+<span>4
</span></span></span><span>=<span><span><span><span>3x</span>+12</span>+<span>10x</span></span>+4
</span></span><span>=<span><span>(<span><span>3x</span>+<span>10x</span></span>)</span>+<span>(<span>12+4</span>)
</span></span></span><span>=<span><span>13x</span>+<span>16
Answer = </span></span></span><span>13x</span>+<span>16
(hope this helps)</span>
Answer:
5/8
Step-by-step explanation:
The probability of not getting blue can be found by dividing the number of sections that are not blue by the total number of sections.
P(not blue)= not blue / total
There are a total of 8 sections. 3 are blue, which leaves 5 that are not blue (1 yellow, 2 red and 2 green).
not blue= 5
total= 8
P ( not blue)= 5/8
This fraction cannot be reduced, therefore our answer is 5/8
So elimination method is basically adding the equations and canceling out variables.
-6x + 6y = 6
-6x + 3y = -12
The eaiest way to solve is by multiplying the bottom equation by -1.
-6x + 6y = 6
6x - 3y = 12
Now you add the eqautions.
3y = 18
Divde 3 from both sides.
y = 6
Now plug in 6 into any of the original two equations. Lets use the first one.
-6x + 6(6) = 6
-6x + 36 = 6
Subtract 36 from both sides.
-6x = -30
Divide -6 from both sides.
x = 5
So your solution is (5, 6).
I hope this helps love! :)
Answer:
hi sister
Step-by-step explanation:
Im also a girl teehee
Given the quadratic function, to get the roots we factorize:
3x²-4x-7=0
3x²+3x-7x-7=0
3x(x+1)-7(x+1)=0
(3x-7)(x+1)=0
thus the roots are
x=-1 or x=3/7
thus the sum of the roots will be:
-1+3/7
=-4/7